PENGARUH WORKPLACE BULLYING TERHADAP PENYEMBUNYIAN PENGETAHUAN YANG DIMODERASI OLEH PENYIMPANGAN MORAL PADA KARYAWAN PERHOTELAN DI KOTA BANDA ACEH - Resthu Hanggasta Hariyonyoto; Murkhana Murkhana (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to determine the effect of workplace bullying on knowledge hiding with moral disengagement as the moderator. Empirical study was conducted on hotel employees at 7 hotels in Kota Banda Aceh using questionnaires as the research instruments. Probability Sampling is used as sampling method with Proportional Random Sampling technique. MRA (Moderated Regression Analysis) method was used as data analysis method using IBM SPSS 22 software. The result of this research shows that workplace bullying has positive and significant effect on knowledge hiding, moral disengagement has positive and significant effect on knowledge hiding, moral disengagement moderates the effect of workplace bullying on knowledge hiding.